Take the 2-minute tour ×
Quantitative Finance Stack Exchange is a question and answer site for finance professionals and academics. It's 100% free, no registration required.

I am sorry if the following question is not quantitative finance.

I am reading this thing badly written lecture notes, which says

$W^r_1 \equiv W_1/P_1^g = (W_0^rP_0^g)(1+R)=/P_1^g$

$(1+R^r)\equiv W_1^r/W_0^r = (1+R)(1+\pi)$

$R^r\equiv \Delta_1^r/W_0^r = (R-\pi)/(1+\pi)$

I am guessing $R^r$ is the rate of real return. $R$ is nominal rate of return and $\pi$ is inflation. but what the hell is $P_1^g$ and $W_1^r$ I don't really understand the first formula in particular.

I am guessing $W_1$ is the wealth at time 1?

share|improve this question
1  
This question appears to be off-topic because interpreting badly-written lecture notes is unlikely to be useful to future visitors. –  Joshua Ulrich Jan 2 at 17:32
add comment

closed as off-topic by Joshua Ulrich, olaker Jan 2 at 19:39

  • This question does not appear to be about quantitative finance within the scope defined in the help center.
If this question can be reworded to fit the rules in the help center, please edit the question.

1 Answer

up vote 3 down vote accepted

I'm guessing ${W_t^r}$ and ${W_t}$ correspond to real and nominal endowment at time $t$, respectively, and that ${P_t^g}$ is the price level at time $t$. In that case, $W_t^r \equiv W_t/P_t^g$ follows, and if endowment grows at a nominal interest rate $R_t$, then $W_t = W_{t-1}(1+R_t)$. We can write $W_{t-1}=(W_{t-1}^rP_{t-1}^g)$, so by substitution $W_t=(W_{t-1}^rP_{t-1}^g)(1+R_t)$.

I suspect the last part of the first line, $=/P_1^g$, contains a typo. There should be no space between this and the previous text: that way we can substitute $W_t$ back into the expression for $W_t^r$ and get to the adequate expression:

$W_t^r = (W_{t-1}^rP_{t-1}^g)(1+R_t)/P_t^g$.

What bugs me is the second line: we can define the inflation rate $\pi_t$ as $P_t^g=(1+\pi_t)P_{t-1}^g$. We are given $(1+R_t^r)\equiv W_t^r/W_{t-1}^r$, so the equation should resolve to:

$\dfrac{W_t^r}{W_{t-1}^r}=\dfrac{W_t/P_t^g}{W_{t-1}/P_{t-1}^g}=\dfrac{W_t}{W_{t-1}}\dfrac{P_{t-1}^g}{P_t^g}=(1+R_t)\dfrac{1}{1+\pi_t}=\dfrac{1+R_t}{1+\pi_t}$

With the above in hand, all we need to do is subtract one to arrive at your final expression:

$R_t^r=\dfrac{1+R_t}{1+\pi_t}-1=\dfrac{1+R_t-(1+\pi_t)}{1+\pi_t}=\dfrac{R_t-\pi_t}{1+\pi_t}$

EDIT: This, of course, is a restatement of the Fisher equation.

share|improve this answer
add comment

Not the answer you're looking for? Browse other questions tagged or ask your own question.